Penerapan Kewenangan Badan Pertanahan Nasional dalam Sengketa Pembatalan Surat Keputusan Pertanahan: Studi Kasus Nomor 56/G/2024/PTUN/PLG) - Afifah Zahra Nadira (Universitas Kuningan, 2025)
The increasing number of land disputes in Indonesia indicates that the administrative decisions of the National Land Agency (BPN) are still frequently questioned, particularly regarding the limits of authority and procedural provisions. Consequently, this topic is critical to research as it creates legal uncertainty for the public. This study formulates two main problems: first, how the BPN's authority in regulating and canceling land decrees operates under positive law; and second, what the form and effectiveness of the BPN's legal defense are in disputes over the cancellation of decisions, specifically in Case Number 56/G/2024/PTUN/PLG. The objective is to determine the basis of the BPN's authority and assess the quality of the legal defense submitted when its decisions are challenged at the State Administrative Court (PTUN). This research employs a normative juridical method with a statutory approach, reviewing the Basic Agrarian Law (UUPA), Government Regulation (PP) No. 24 of 1997 and its amendments, and Law No. 30 of 2014. The results indicate that the issuance of the Land Ownership Certificate in Case No. 56/G/2024/PTUN/PLG was proven to have exceeded the territorial jurisdiction of the Palembang BPN and was deemed procedurally flawed. Therefore, the BPN's legal defense failed to refute the element of abuse of authority. This finding emphasizes the urgent need to improve procedural compliance and professionalism in land administration.